Nota sobre la distribución geográfica y morfología de Manfreda involuta (Agavaceae) - Rodríguez, Aarón; Carrillo-Reyes, Pablo; Castro-Castro, Arturo (Instituto de Ecología, A.C., 2008)
As a result of recent botanical collections in western Mexico, the known geographical distribution of Manfreda involuta is extended and its morphological description completed. The species is endemic to western Mexico.